A systematic mapping study on digital game adaptation dimensions - Carvalho, Caio; Teran, Luciano; Mota, Marcelle; Pereira, Roberto (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2022: Anais do XXI Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2022)
Designing accessible digital games requires considering social, technical, and cultural aspects according to the diversity of the target audience. One way to address this diversity of audiences to promote accessibility is through adaptability, allowing a game to be customized according to the needs of its users. A Systematic Mapping Study was conducted to identify and document studies dealing with the adaptation of digital games according to the needs of their users. This paper focuses on the Mapping research questions on the following adaptation dimensions: (1) What game aspects are being adapted? (2) Why is it being adapted? (3) For whom is it being adapted? (4) When does the adaptation occur? and (5) Who is carrying out the adaptation? The main results of this study are: (i) the identification of a trend in research on adaptive systems; (ii) the use of Dynamic Difficulty Adjustment and Procedural Content Generation techniques to implement adaptive behaviour in games; (iii) the patients, non-specified users, and health professionals categories as the main results in the studies' target audience.